Finding the "Pacman" in you Pagtuklas ng "Pacman" sa iyong sarili - Antonio, Charito A. (Lampara books, 2013)
"A chick is born lacking in the qualities of good fighter and becomes the butt of jokes of all those who see him. He is adopted by a little boy who gives him the monicker "Pacman". Find out in this story why the chick is christened "Pacman," and the right attitude towards overcoming or filling in one's deficiency and proving one's worth."